Competence of Autistic Children in the Able to Educate Group in Pronunciation of Basic Vocabulary - Heru Pratikno; Dadang Sudana; Kokok Dj Purwanto; Diden Rosenda (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
In interpersonal communication, language skills are important to improve. However, this is difficult to apply to children with special needs, such as autism. Therefore, the purpose of the study is that the author wants to know the extent to which autistic students are able to articulate phonetic sounds and basic words correctly. In addition, this study also aims to determine the ability of sufferers to understand a concept instructed by the teacher. For this research method, the approach used is a qualitative study. Data collection was carried out by observation, interviews, and documentation of autistic students' speech accompanied by their teachers. Furthermore, the collected data will be analyzed. Data analysis was carried out using a qualitative descriptive method with a psycholinguistic analysis knife of the theory of child language acquisition, production, and use. The results of the study showed that autistic students with the category of being able to learn have better language skills. They can pronounce similar bilabial sounds, such as /p/ and /b/, count, and recognize concepts with instructions although they are still imperfect. Of course, this is caused by the child's lack of focus because there are other things he wants.